Konstruksi Citra Keluarga melalui Public Relation Organisasi - Ahmad Nadhim Ayatullah; Oji Kurniadi (UNISBA Press, 2022)
Abstract. Drama is an audio-visual work that uses television as its transmission medium. The average duration per episode is 60 – 90 minutes and airs once a week. The story in the drama is usually interesting and ends with a certain memory statement so that the audience can continue the next episode to understand the ending of the drama. South Korea is one of the developed countries that doubles its creative industry, such as K-pop music dramas and films, the Korean government also contributes to the creative arts industry. And in 2020 until now there has been an increase in Korean drama audiences in the world, judging by the effects of the pandemic, which makes people have to do everything at home. This study aims to describe the construction of the family image represented in the Korean drama